2014
DOI: 10.1038/nm.3542
|View full text |Cite
|
Sign up to set email alerts
|

The microbiota regulates neutrophil homeostasis and host resistance to Escherichia coli K1 sepsis in neonatal mice

Abstract: Acquisition of microbes by the neonate, which begins immediately during birth, is influenced by gestational age and mother’s microbiota and modified by exposure to antibiotics1. In neonates, prolonged duration of antibiotic therapy is associated with increased risk of sepsis after 4 days of life, known as late-onset sepsis (LOS)2, a disorder critically controlled by neutrophils3, but a role for the microbiota in regulating neutrophil behavior in the neonate has not been described. We exposed pregnant mouse dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
446
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 476 publications
(472 citation statements)
references
References 45 publications
20
446
2
4
Order By: Relevance
“…Because IL-17 is upstream of G-CSF 52,53 , lower levels of IL-17 equate to reduced expression of G-CSF and steady-state release of neutrophils from the bone marrow 46 . Commensal bacteria and enterocyte-derived CXCL5 in the gut also play a role in neutrophil homeostasis by increasing or inhibiting IL-17 production, respectively 54,55 . IL-1β that is released from dying cells or upregulated in response to inflammatory stimuli is another potent inducer of the IL-17-G-CSF axis 56,57 .…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…Because IL-17 is upstream of G-CSF 52,53 , lower levels of IL-17 equate to reduced expression of G-CSF and steady-state release of neutrophils from the bone marrow 46 . Commensal bacteria and enterocyte-derived CXCL5 in the gut also play a role in neutrophil homeostasis by increasing or inhibiting IL-17 production, respectively 54,55 . IL-1β that is released from dying cells or upregulated in response to inflammatory stimuli is another potent inducer of the IL-17-G-CSF axis 56,57 .…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…Because of the lack of direct contact with live microbes, it has long been presumed that the microbiota does not influence these systemic defences. We now know that this assumption is incorrect and that the production and function of cells that constitute systemic defences is greatly influenced by the microbiota 29, 30, 39, 66, 67, 68…”
Section: Host Resistance To Systemic Infection and The Microbiotamentioning
confidence: 99%
“…Reduced neutrophil production renders these animals more susceptible to systemic infection by numerous bacteria including E. coli and Listeria monocytogenes 39, 69. Studies have shown that recognition of bacteria and/or bacterial products from the microbiota by PRRs is the first step in driving this microbiota‐dependent increase in neutrophil production 67, 69. This PRR activation is not restricted to a single site, as PRR ligands in the circulation and at the mucosa are able to drive increased neutrophil production 67, 69.…”
Section: Host Resistance To Systemic Infection and The Microbiotamentioning
confidence: 99%
See 2 more Smart Citations